The Influence of the Arabic Language on Language Development (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article provides information about the existence of the Arabic word in the lexicon of the Uzbek language, the occupation of the Central Asian territories by the Arabs in the past, and its historical and social consequences. As a result, the spread of the Arabic language, the need to write, read, communicate and perform religious beliefs in this language led to the acquisition of the Arabic language by the local people to a certain extent.